Investigations into the lack of consensus in the reporting of HLA antibody specificities in the UK. Issue 3 (27th February 2009) - Wortley, A; Mckinley, K; Whittle, R; Calvert, A; Shaw, O; Fernando, R; Pearse, A; Hopkins, K; Clark, B
Abstract : Aims: Lack of consensus in HLA antibody reporting in proficiency schemes has previously been attributed to a number of differing factors. This study was set up to eliminate the majority of these factors by reducing analysis to a pure data handling exercise. Methods: Anonymised raw data files for LABScreen Single Antigen class I and II and related patient information were provided to seven participating centres. The centres reported back the HLA antibody specificities according to their single antigen bead reporting policy. Details of the reporting policy of each centre were retrospectively requested by questionnaire. Results: The number of HLA antibody specificities reported by the different centres varied widely. Software analysis called more HLA antibody specificities than any of the centres. None of the centres matched consensus for reported HLA class I specificities on any of the datasets, and no two centres reported the exact same HLA class I antibody profile; consensus was reached by one centre for HLA class II antibody specificities reported from two of the datasets. Retrospective review found data handling practice between centres to vary widely. Conclusions: Lack of agreement exists between UK centres in regard to HLA antibody specificity analysis. The fact that the required analysis was limited to interrogation of supplied data files makes the observation more concerning. The root cause of this variation is differences in data handling practice between the participating centres.